Disclosures of conflicts of interest in clinical practice guidelines - Red Thaddeus D. Miguel; Maria Asuncion A. Silvestre; Ma Lourdes A. Salaveria-Imperial; Maria Teresa S. Tolosa; Gina Antonina S. Eubanas; Leonila F. Dans (Elsevier, 2021)
Problem considered: Despite promotion for adequate declarations of conflicts of interests (COI), clinical practice guidelines (CPGs) continuously fail to provide suitable statements. It was our aim to investigate the frequency of COI reporting in Philippine CPGs and possible associations of COI disclosure and use of the Grading of Recommendations, Assessment, Development and Evaluation or GRADE methodology. Methods: Eighty-seven CPGs developed in the Philippines before 2017 were appraised for adequate COI disclosures using Item-23 of the AGREE II instrument. Explanatory variables included indications of use of GRADE, professional organization that led the development of the CPG, and year of CPG completion. Results: Only 12 CPGs (13.8%) had a COI score above the base COI score, with a mean COI score of 5.5 (SD: 1.5). COI disclosure was not statistically different between CPGs that reported or did not report using GRADE (p = 0.2196). Similarly, there was no difference in COI reporting by surgical versus non-surgical organizations (p = 0.5264). The increase in the number of Philippine CPGs was strongly correlated with COI reporting (r = 0.82, p = 0.0001). There was a steady increase of COI reporting through the years, from 5.3% in 1999-2006 to 35.3% in 2016 (p = 0.03427). Conclusion: Despite improving levels of compliance in reporting COIs in recent years, the overall number of disclosures remain low even when GRADE methodology was reportedly implemented. The findings indicate the need for better GRADE training, a clearinghouse for monitoring disclosures, and future studies on the impact of COI disclosures on quality of recommendations.